Reverse phase-high performance liquid chromatography method estimation of levocetirizine and montelukast in tablet dosage forms - Mala Swapna; Srikanth Choudary Pallothu (International Journal of Pharmacy and Analytical Research, 2022)
In the current study a simple, accurate and precise reverse phase liquid chromatographic method has been developed for simultaneous estimation of Levocetirizine Hydrochloride and Montelukast Sodium from tablet dosage form. The method was developed using HPLC series Compact System Consisting of Inertsil-C18 ODS column, using a mixture of 0.05 (M) Potassium Dihydrogen Phosphate Buffer and Methanol : buffer (80:20) as mobile phase in an isocratic elution mode at a flow rate of 1.0 ml/min, at 30ºC with a load of 10µl. The detection was carried out at 225 nm. The retention time of Levocetirizine and Montelukast were found to be around 2.8 min and 43.9 min respectively. The method was validated with respect to linearity, robustness, precision and accuracy and was successfully applied for the simultaneous quantitative determination of Levocetirizine Hydrochloride and Montelukast Sodium from the tablets.